Pengaruh Sosialisasi Pajak, Pengetahuan Pajak dan Sikap Love of Money Terhadap Kepatuhan Wajib Pajak Orang Pribadi - Gine Das Prena; Puhantania Putuhena (Universitas Matana, 2022)
The study is a study that USES a quantitative approach using a questionnaire as a tool for collecting primary data from the respondents. The population within the study is 131,312 effective, registered, private, private, and the samples used in the study number 100 personalized individuals registered to the west mataram primary sampling office by technical sampling where the sample is chosen by chance to look at the predetermined criteria for individual tax taxpayers. The data analysis used in the study is linked to linear regression using the help of the IBM SPSS 24.0 for Windows application. The results of research indicate significant results in unmitigated tax variables and the attitude of love of money. And the negative results are not significant to the conformity of personal taxpayers to the primary role of western mataram.